Changes in alcohol use during the COVID‐19 pandemic and previous pandemics: A systematic review. (12th April 2022) - Sohi, Ivneet; Chrystoja, Bethany R.; Rehm, Jürgen; Wells, Samantha; Monteiro, Maristela; Ali, Shehzad; Shield, Kevin D.
Abstract: The objective of this study is to summarize the research on the relationships between exposure to the COVID‐19 pandemic or previous pandemics and changes in alcohol use. A systematic search of Medline and Embase was performed to identify cohort and cross‐sectional population studies that examined changes in alcohol use during or following a pandemic compared to before a pandemic occurred. Outcomes examined included differences in the volume and frequency of alcohol consumption and the frequencies of heavy episodic drinking (HED) and alcohol‐related problems during a pandemic compared to before a pandemic. Quality assessment was performed using the Cochrane Risk of Bias Tool for Nonrandomized Studies. This study was performed according to the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses guidelines. The search yielded 672 articles; 27 were included in the narrative review, of which 6 were cohort studies (all from high‐income countries). A total of 259, 188 participants were included. All cohort studies examined the impact of COVID‐19 and associated pandemic‐related policies, including social distancing and alcohol‐specific policies, on alcohol use. Cohort studies demonstrated a consistent significant decrease in total alcohol consumption (Australia) and a significant increase in the frequency of alcohol use (United States). A significant decrease in the frequency of HED was observed in Australia and Spain but not in the United States. A significant increase in the proportion of people with problematic alcohol use was observed in the United Kingdom. Initial insights into changes in alcohol use indicate substantial heterogeneity. Alcohol use may have decreased in some countries, while HED and the proportion of people with problematic alcohol use may have increased. The lack of high‐quality studies from low‐ and middle‐income countries reflects a dearth of information from countries inhabited by most of the world's population. Abstract : A systematic search of studies examining changes in alcohol use during or following pandemics compared to before a pandemic occurred identified 7 cohort and 21 cross‐sectional studies. Alcohol use may have decreased in some countries and remained constant in others. Heavy episodic drinking and problematic alcohol use may have increased in some countries and remained stable in others. Additionally, the lack of studies from low‐income countries indicates a dearth of information for most of the world's population.